Inclusive States : Social Policy and Structural Inequalities - Dani, Anis A. (Washington, DC : World Bank, 2012)
This series New Frontiers of Social Policy aims to promote social development through systematic attention to the underlying social context and the social outcomes of development interventions and public policy. It compels the reader to think of social policy in terms of increasing access to productive assets, infrastructure, and goods and services; strengthening governance and accountability; enabling the rights and obligations of citizens to promote equitable access to development opportunities; and managing the social dimensions of conflict, natural disasters, and climate change. It recognizes the central role of social policy in ensuring that development policies and programs are sustainable. This book series has been conceived and produced for the broader development community, rather than for social policy specialists alone. This book places particular emphasis on, and attempts to overcome, the underlying causes of structural inequalities whereby social groups based on ethnicity, race, tribe, gender, or cultural differences are systematically disadvantaged compared with other groups with which they coexist. These inequalities prevent many developing countries from realizing their full potential and may undermine the sustainability of development outcomes.